Syriac idiosyncrasies : theology and hermeneutics in early Syriac literature - Ruzer, Serge. (Jerusalem Studies in Religion and Culture, 2010)
The study of early Syriac Christianity has for decades been steadily expanding, yet its scope still lags way behind that of research relating to Greek and Latin Christianity. One of the intriguing and understudied topics here is the nature of Syriac Christianity's autonomous identity in late antiquity. This question is intrinsically connected to its genesis from an indigenous Christian Aramaic background as well as its interaction with the neighboring Jewish milieu. This volume unearthes some of the idiosyncracies -- mainly pertaining to trinitarian theology, christology and hermeneutics -- to be found in early Syriac literature before the onslaught of Greek hegemony. The idiosyncrasies analyzed here offer new insights into the nature of that peculiar brand of early Christianity, confirming a model of an indigenous early Syriac tradition gradually entering into a dynamic interaction with Greek influence.